Immuno-informatics Analysis to Identify Novel Vaccine Candidates and Design of a Multi-Epitope Based Vaccine Candidate Against Theileria parasites - Kar, Prajna Parimita; Srivastava, Anand (Frontiers in Immunology, 2018)
Theileriosis poses a serious threat to ruminants in tropical and subtropical countries. It is a tick-borne disease, caused by an apicomplexan parasite, Theileria. The high disease burden in animals causes huge economic losses to marginal farmers. Further, with increasing cases of resistance to commonly used drugs, it is highly desirable to develop better and cost-effective vaccines against theileriosis. The only available vaccine, live attenuated parasite vaccine, has many drawbacks and hence is unsuitable for controlling this disease. Immuno-informatics has emerged as a useful tool in down selection of potential molecules for vaccine development. In this study, we have used an immuno-informatics driven genome-wide screening strategy to identify potential vaccine targets containing important and effective dominant immunogens against Theileria. The proteome of Theileria annulata was screened for proteins with probability of plasma membrane localization or GPI anchor. The proteins non-homologous to the host (bovine) were selected and their antigenicity was analyzed. The B-cell epitopes were identified in the selected proteins and mapped in the modelled structure of the proteins. A total of nineteen linear epitopes in twelve proteins, exposed in the extracellular space and having the potential to induce protective antibodies were obtained. Additionally, CTL epitopes which are peptides with 9-mer core sequence, were also identified, modelled and docked with bovine MHC-I structures. The CTL epitopes showing high binding energy with the bovine MHC-I were further engineered in silico to design a putative multi-epitope vaccine candidate against Theileria parasites. The docking studies and molecular dynamics studies with the predicted multi-epitope vaccine candidate and modelled bovine TLR4 exhibited strong binding energy, suggesting that the complex is stable and the putative multi-epitope vaccine candidate can be a potentially good candidate for vaccine development.